If walls could talk eaudiobook - Blackwell, Juliet (Haunted Home Renovation, 2013)
Melanie Turner has made quite a name for herself remodeling historic houses in the San Francisco Bay Area. But now her reputation may be on the line. At her newest project, a run-down Pacific Heights mansion, Mel is visited by the ghost of a colleague who recently met a bad end with power tools. Mel hopes that by nailing the killer, she can rid herself of the ghostly presence of the murdered man—and not end up a construction casualty herself . . .